Training of alphanumeric filing system and electronic filing to teachers and administrative staffs of junior high school in Dolok Ilir - Sianipar, Sariartha; Silalahi, Amlys Syahputra; Yuliaty, Tetty; Dalimunthe, Doli Muhammad Ja'far; Siringoringo, Yan Batara Putra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The archiving process uses a certain system in the preparation, maintenance of records so that they can be recovered quickly and precisely and easily for destruction of archives based on certain criteria. The archive itself has enormous benefits for educational organizations, because the archive is information on activities carried out by schools. Archives in schools need to be well managed, so that archives can be used effectively and efficiently and have good accessibility. The arrangement of archives usually has several problems including, documents cannot be recovered because they are lost, the number of documents is always increasing every day, the storage area for documents is too small compared to the number of documents, so the space is insufficient, not to mention the lack of staff capacity, and the system. The storage is not in accordance with the principles of archiving. For this reason, this service is aimed at providing knowledge and skills in arranging archives in accordance with RI archiving principles, namely using an alphanumeric archive storage system, through training followed by practice and evaluation. Adequate archive facilities and infrastructure are needed in schools for this training. After the dedication was carried out, teachers and administrative staff experienced an increase in knowledge and skills in compiling personal archives and schools got the facilities and infrastructure that supported archiving. Furthermore, an evaluation of the application of archiving in schools is carried out in order to determine its effectiveness in school management.